Assessment of Carbon Sequestration Potential of Agroforestry System in Pothwar: Opportunities and Challenges - Zia, Muhammad Noman; Malik, Sabeeqa Usman; Ahmad, Owais; Usman, Hazrat; Khan, Muhammad Junaid; Shah, Muhammad Aamir (Journal of Agriculture and Biology, 2025)
Agroforestry has been recommended as a carbon sequester for the region where carbon emission is prominent. Agroforestry is acknowledged as a natural approach to carbon sequestration, playing a crucial role in enhancing carbon sinks. In Pakistan, agroforestry practices have maximized the sinks of carbon on higher level playing a vital role in mitigation of climate change.  The current research work focused on the role of agroforestry systems in carbon mitigation. Agroforestry provides various opportunities to fulfill the objectives of the climate adaptation. During our research, A focused on the biomass of the trees, carbon sequestration potential in agroforestry practices at rural and urban sites.  Industries and urbanization are the foremost carbon emission sources in the surroundings. Recently the nature-based solution has promoted to provide solution to the climatic adaptations. The results depicted that Dalbergia sissoo showed higher concentration of carbon in the urban sites (2.58, 0.56, and 4.57 Mg ha−1) and outside sites from the urban vicinity. In terms of total carbon stock and carbon sequestration, Syzygium cumini and Acacia nilotica were the most prominent species within urban sites, with values of 2.82 and 10.32 Mg ha−1, respectively, and 3.78 and 13.5 Mg ha−1 in rural sites. Conversely, Eucalyptus camaldulensis exhibited higher carbon stock and sequestration values in rural vicinity sites, showing 7.83 and 28.70 Mg ha−1. Sites outside the urban vicinity generally had lower carbon stock and sequestration values. Among the trees studied, Dalbergia sisso was the most dominant in the urban vicinity with values of 0.97 and 3.54 Mg ha−1. In Chakwal, Ficus religiosa showed notable values of 1.26 and 4.63 Mg ha−1, while in the cosmetic industry sector, Vachellia nilotica had the highest values, 2.51 and 9.19 Mg ha−1, compared to other species.  Analysis of belowground biomass and carbon storage revealed a decrease in soil carbon with increasing depth, with the highest soil carbon stock found at a 0–20 cm depth both inside and outside the industries.  The study concludes that agroforestry practices within and around various rural and urban sites hold significant potential for mitigating air emissions.
Keywords: Carbon sequestration; Air pollution; Rural; Urban; Pothwar